Pengaruh Penambahan Fiber Selulosa CF-31500 Terhadap Durabilitas Campuran AC-BC: Studi Eksperimental Berbasis Indeks Kekuatan Sisa - Aminsyah, Muhammad (Jurnal Bangunan, Konstruksi & Desain, 2025)
Road pavement construction often experiences damage due to decreased durability by high traffic volumes, changing temperatures and weather can reduce the quality of road pavement construction such as cracks, distortions, surface defects and other road damage. Based on this, a study was conducted on the use of CF-31500 fiber additives on the durability of the Asphalt Concrete–Binder Course (AC-BC) mixture. This study aims to determine the effect of CF-31500 fiber additives on the durability of the AC-BC asphalt concrete mixture. In this study, CF-31500 fiber additives were used as much as 0.3% of the total weight of the mixture. Durability research used the Marshall test with immersion variations of 0, 1, 4, 7, 14 days with 3 samples per variation. In the durability of the asphalt mixture, the Residual Strength Index (IKS) indicator was used. The IKS value requirement according to the 2018 Bina Marga general specifications is  90%. The results showed that the durability of the standard AC-BC mixture still met the specifications at a 4-day immersion duration. The durability of the AC-BC mixture with the addition of Fiber CF 31-500 still meets the specifications at a soaking duration of 10 days. The durability of the AC-BC mixture with the addition of Fiber CF 31-500 is higher than the durability of the standard AC-BC mixture, with an increase of 1.5 times from 4 days to 10 days. This proves that the mixture with the addition of the CF-31500 fiber additive is more durable than the mixture without the addition of the additive.